Body composition at birth: A hospital based study - Poonam Patel, *Suneeta Chandorkar and (Food Biology, 2011)
The present hospital based study was a situational analysis to study the anthropometric and body composition parameters of the neonates of Vadodara city and to examine the maternal factors associated with it. Maternal obstetric history and anthropometric measurements (weight and height) were recorded. Birth weight of the neonates was recorded immediately after delivery. Length, MUAC and triceps and supra iliac SFT of the neonates was measured within 48 hours of delivery. Pregnant women had poor nutritional status with 71% weighing < 60 kg and 63% anemic. The overall incidence of low birth weight was 30.79% (57% in LIG and 18% in MIG). Normal birth weight neonates had significantly higher mean anthropometric and body composition parameters as compared to the low birth weight neonates (pÃ¢â€°Â¤0.000). Birth weight and anthropometric indices positively correlated with the measures of body composition (pÃ¢â€°Â¤0.01). The poor maternal nutritional status resulted in adverse birth outcome. Highest incidence of chronic severe malnutrition (low head circumference for age Z-score) was seen followed by wasting. The neonates had low muscle mass and fat mass unlike the typical Ã¢â‚¬Å“Asian thin fat phenotypeÃ¢â‚¬Â.